Evaluation of an innovative multi-cancer early detection test: high sensitivity and specificity in differentiating cancer, inflammatory conditions, and healthy individuals - Walter, Nike; Groth, Jörg; Zwerger, Berthold von und zu (Frontiers in Oncology, 2025)
BackgroundCancer is a leading cause of death worldwide, with early detection crucial for effective treatment. Traditional diagnostic methods, such as imaging and biopsies, are often limited by invasiveness, cost, and sensitivity. Blood-based multi-cancer early detection (MCED) tests offer a less invasive and potentially more comprehensive approach. Recently, a novel screening tool, the Carcimun® test was reported, detecting conformational changes in plasma proteins through optical extinction measurements. This study evaluates the Carcimun® test’s performance, including participants with inflammatory conditions.MethodsThis prospective, single-blinded study included 172 participants: 80 healthy volunteers, 64 cancer patients (various types), and 28 individuals with inflammatory conditions (fibrosis, sarcoidosis, pneumonia) or benign tumors. Plasma samples were analyzed using the Carcimun® test. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated.ResultsMean extinction values were significantly higher in cancer patients (315.1) compared to healthy individuals (23.9) and those with inflammatory conditions (62.7) (p<0.001). The Carcimun® test distinguished these groups with high accuracy (95.4%), sensitivity (90.6%), and specificity (98.2%). Significant differences were found between healthy participants and cancer patients (p<0.001), and between cancer patients and those with inflammation (p<0.001).ConclusionThe Carcimun® test achieved high accuracy, sensitivity, and specificity, effectively identifying cancer patients while minimizing false positives and negatives. By including participants with inflammatory conditions, we addressed a significant limitation of previous studies, demonstrating the test’s robustness in real-world clinical scenarios. These findings underscore the potential of the Carcimun® test as a valuable tool for early cancer detection and screening.